New Clues to Understanding HIV Nonprogressors: Low Cholesterol Blocks HIV Trans Infection - Vinayaka R. Prasad (American Society for Microbiology, 2014)
ABSTRACT A small percentage of HIV-infected subjects (2 to 15%) are able to control disease progression for many years without antiretroviral therapy. Years of intense studies of virologic and immunologic mechanisms of disease control in such individuals yielded a number of possible host genes that could be responsible for the preservation of immune functions, from immune surveillance genes, chemokines, or their receptors to anti-HIV restriction factors. A recent mBio paper by Rappocciolo et al. (G. Rappocciolo, M. Jais, P. Piazza, T. A. Reinhart, S. J. Berendam, L. Garcia-Exposito, P. Gupta, and C. R. Rinaldo, mBio 5:e01031-13, 2014) describes another potential factor controlling disease progression: cholesterol levels in antigen-presenting cells. In this commentary, we provide a brief background of the role of cholesterol in HIV infection, discuss the results of the study by Rappocciolo et al., and present the implications of their findings.